(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To study and describe the activities of population collaborators in the newly merged communes of Dau Tieng district, Ho Chi Minh city after the merger of the two-tiered local government model. Subjects and methods: This study was conducted using a descriptive, cross-sectional design on 89 health workers currently working in the newly established communes of the Dau Tieng area, by using a pre-prepared set of interview questions for the population collaborators. Results: Research shows 79.8% of population collaborators are Kinh ethnic group, with one collaborator managing 771 people. Data management work mainly involves initial record-keeping related to health, accounting for 70.8%. Up to 82% of population collaborators are involved in communication, advocacy, and counseling activities for the people; simultaneously, 85.4% of collaborators are responsible for monitoring and tracking contraceptive methods in the locality. Although 94.4% of collaborators believe the current remuneration is inadequate, 80% still wish to continue working. Therefore, the attention and support of all levels of government are needed to ensure that population collaborators can work with peace of mind, and to achieve effective healthcare for the people, contributing to improving the quality of life of the local community. Conclusion: Population collaborators play a vital role in the national development strategy, closely linked to key socio-economic issues. The participation of this workforce is indispensable for effective population work. Therefore, attention and support from all levels of government are essential to help collaborators feel secure in their work, improve the effectiveness of public health care, and contribute to improving the quality of life in their localities.